النسوية في الخطاب الروائي السيرذاتي المغاربي- قراءة في نماذج مختارة - نصيرة زلازلي (جامعة البليدة2؛كلية الاداب واللغات, 2025)
الذي تأثر بالأطروحات ، ا للفكر النسوي ً ا واسع ً شهد العالم العربي والمغاربي انتشار الغربية وامتد إلى مختلف المجالات، بما في ذلك الأدب والفن. وقد أدى هذا الانتشار إلى انخراط العديد من الكاتبات في نمط من الكتابة الإبداعية التي تحمل بصمة نسوية واضحة، حيث تميزت بنقد السلطة الذكورية، والاحتفاء بالجسد الأنثوي، وتقديم رؤية خاصة للعالم تعكس تجاربهن الذاتية. في هذا السياق، تسعى هذه الدراسة الموسومة بـ"النسوية في الخطاب الروائي السيرذاتي المغاربي - قراءة في نماذج مختارة" إلى استكشاف تجليات النظرية النسوية ، داخل السرد الذاتي، من خلال تحليل تجارب شخصية تداخلت مع قضايا النساء ومشكلاتهن في محاولة للإجابة عن تساؤل جوهري: هل نجحت الكتابات النسوية المغاربية في بلورة خطابها المستقل، النابع من عمق الواقع الاجتماعي والثقافي لبلدانها، أم أنها كانت مجرد صدى للأفكار الغربية، دون أن تحمل خصوصية محلية تعكس قضايا أمتها وتطلعاتها؟ Abstract : The Arab and Maghreb world has witnessed a widespread expansion of feminist thought, influenced by Western theories and extending into various fields, including literature and art. This expansion has led many female writers to engage in a form of creative writing that bears a distinct feminist imprint, characterized by criticism of patriarchal authority, the celebration of the female body, and the presentation of a unique worldview reflecting their personal experiences. In this context, this study, titled "Feminism in Maghrebi Autobiographical Fiction – A Reading of Selected Works," aims to explore the manifestations of feminist theory within self-narratives by analyzing personal experiences intertwined with women's issues and struggles. It seeks to answer a fundamental question: Have Maghrebi feminist writings succeeded in shaping an independent discourse rooted in the social and cultural realities of their societies, or have they merely echoed Western ideas without developing a distinct local identity that reflects the concerns and aspirations of their nations?
Keywords: السردية في الخطاب الرو; السير الذاتي المغاربي